Economical and technical comparison of valve ceramics available in Turkish market - Palaci, Yuksel (WILEY, 2020)
In this study, ceramic valves, used in faucet cartridges, were studied, considering that the market size is nearly 12 million per year. Six different alumina ceramic valves from various companies in Turkey were analyzed through physical and mechanical tests such as measurement of density, and surface roughness and hardness. Their chemical compositions and microstructures were analyzed by scanning electron microscopy (SEM). The results showed that the density values, surface roughness, and surface hardness were between 3.66 and 3.84 g/cm(3), 0.13 and 0.22 mu m (Ra), and 805 and 1217 HV, respectively. Among the six valves, while valve 4 had the highest, valve 6 had the lowest hardness and density. Moreover, a direct correlation between the estimated wholesale and retail prices was not observed. The valves designated as 5 and 6 had the lowest prices and the valve 2 had the highest price. They had the similar technical properties satisfying Turkish and European standards.
Keywords: alumina; ceramic engineering; faucet cartridge; properties; WEAR; FRICTION; Materials Science